Agent technology for acquiring, monitoring and process control systems in distributed architectures - Dorao, Carlos Alberto (2001)
The industrial plants s uch as the power plant, in particular the nuclear ones, have presented important changes in the conditions during the last 20 years. This situation led to the evaluation of the emergent t echnology of agents for developing d istributed acquiring, monitoring and p rocess control systems, according to the necessities of the medium and large size plants that present critical processes. To the feasibility analysis, a prototype was developed with the goal of evaluating advantage and disadvantage of agent t echnology. From another point of view this permits to identify the complementary technology and the involved problems in the development of this systems. This system was divided into subsystems and components with the aim of getting modular and reusable software. Different modulus were integrated in a generic architecture composed of four sub systems: Field, Supervision, Information and External System.